Analisis Pengembangan Program Kesehatan Jiwa Masyarakat di Puskesmas Tombulu - Citra W. Thamrin; Erling D. Kaunang; Gustaaf A. E. Ratag (Medical Scope Journal, 2023)
Abstract: Condition of mental health problems is reflected in its impact including a high enough number of people with mental disorders associated with a high economic burden. This study aimed to analyze the community mental health program at Tombulu Health Center and its obstacles in implementing the program. This was a qualitative and descriptive study. Data were obtained through interviews with informants. The results showed that the mental health program was implemented through a home visit program with health examination, monitoring patient progress, and counseling about family involvement in the treatment. Obstacles experienced in implementing this program included the community's stigma against the patients, therefore, the community and families were less involved in the healing process. Efforts to develop the mental health program included increasing family and community involvement in the treatment process, number of health cadres, and mental health promotions. In conclusion, implementation of the mental health program at Tombulu Health Center in the treatment processs of patients is carried out through home visits, early detection program, and screening to identify mental health problems for the community and health workers. Obstacles include the absence of family support, negative stigma from the community, lack of supporting facilities and infrastructure for the patients, and the hospital location which is quite far away. Keywords: mental health; development of community mental health program   Abstrak: Kondisi masalah kesehatan jiwa tercermin dari dampak yang ditimbulkannya, antara lain angka yang cukup tinggi dari orang dengan gangguan jiwa (ODGJ) diikuti beban ekonomi yang tinggi. Penelitian ini bertujuan untuk menganalisis program kesehatan jiwa masyarakat di Puskesmas Tombulu serta hambatan yang dihadapi dalam  pelaksanaan program tersebut. Jenis penelitian ialah deksriptif kualitatif. Data penelitian diperoleh melalui wawancara dengan informan. Hasil penelitian menunjukkan program kesehatan jiwa dilaksanakan melalui program kunjungan rumah (home visit), disertai kegiatan pemeriksaan kesehatan, pemantauan perkembangan pasien serta penyuluhan tentang keterlibatan keluarga dalam proses pengobatan dan penyembuhan ODGJ. Hambatan yang dialami antara lain stigma dari masyarakat terhadap ODGJ sehingga masyarakat dan keluarga kurang terlibat dalam proses penyembuhan ODGJ. Upaya pengembangan program kesehatan jiwa antara lain dengan meningkatkan keterlibatan keluarga dan masyarakat dalam proses perawatan ODGJ, menambah jumlah kader kesehatan, dan meningkatkan upaya promosi kesehatan jiwa. Simpulan penelitian ini ialah pelaksanaan program kesehatan jiwa di Puskesmas Tombulu dilakukan melalui kegiatan kunjungan rumah (home visit), program deteksi dini, serta skrining untuk mengenali masalah kesehatan jiwa baik bagi masyarakat maupun tenaga kesehatan. Hambatan meliputi tidak adanya dukungan keluarga, stigma negatif dari masyarakat, kurangnya sarana dan prasarana pendukung untuk pasien ODGJ, dan letak rumah sakit yang cukup jauh. Kata kunci: kesehatan jiwa; program pengembangan kesehatan masyarakat